Bi-objective optimisation model with societal constraints for green closed loop supply chain network - a case of battery industry. (2nd August 2019) - Sherif, S. Umar; Sasikumar, P.; Asokan, P.; Jerald, J.
Scrap-battery collection, recovery and new-battery production activities in the battery industries have increased a large quantity of materials and products distribution between the facilities. This situation leads to the sustainability issue in terms of higher transportation cost, greenhouse gas (GHG) emission and drivers fatigue (long driving). In order to address the sustainable issues, the present closed loop supply chain network (CLSCN) is customised. The objective of this paper is to develop bi-objective multi product multi echelon multi period green CLSCN model with societal constraints (GCLSCN-SC) to minimise: 1) the sum of distribution centres' (DC) storage capacity expansion cost and transportation cost; 2) the GHG emission (CO2 and NOx ). The storage capacity expansion strategy and the transportation strategy are established in the proposed model to stimulate the bi-directional flow of the products and materials between facilities and the model is solved by using GAMS-23.5. The performance of proposed model has been compared with the present model and the evaluation demonstrates that the proposed model is efficient. The analysed results of the proposed model under different scenarios are presented in this paper.